Passiones anim{u0BDF}cper Renatum De Cartes: Gallic{u1960}ab ipso conscripte, nunc autem in exterorum gratiam Latina civitate donate. - Descartes, Rene, 1596-1650; Descartes, Ren 1596-1650.; Descartes, Ren 1596-1650. ([Netherlands] : Elsevier, 2014)
RenDescartes' (1596-1650) Passiones Animae or Passions of the Soul, the last of his works, was originally published in French, but was translated into Latin for this Elzevier edition. Descartes builds upon what was previously written about the'passions', which had been a subject for discussion since the time of Plato. Since the modern period, the passions are known as human emotions. According to Descartes' theory, the passions attack the soul and force the body to commit certain, sometimes inappropriate actions.
'First published by Louis Elzevier in 1650. Republished by Elsevier B.V. in 2014.'
Online resource; title from PDF title page (ScienceDirect, viewed March 30, 2015).
Elsevier
Keywords: Emotions -- Early works to 1850.; Mind and body -- Early works to 1800.; Emotions; Mind and body; Electronic books; Early works